Analysis Of The Implementation Of Enterprise Risk Management (ERM) at Zeribowl Group Medan - Tanjung, Ayu Wulandari (Indonesian Journal Publisher, 2025)
This study aims to see how the implementation of Enterprise Risk Management (ERM) in Zeribowl Group Medan Company. This study is a field research using a descriptive qualitative approach. From the results of the study it is known that Enterprise Risk Management (ERM) in Zeribowl Group Company is implemented through eight frameworks including, internal environment, strategic and risk objectives setting, event identification, risk assessment, risk response, control activities, information and communication, monitoring. In addition, through a comprehensive ERM, Zeribowl Group is committed to ensuring that existing risks can be managed effectively, so that the company can focus more on achieving its strategic goals while maintaining the integrity and resilience of the business in the long term.